Analisis Implementasi Kebijakan Harga Transfer Pada CV ABC Yogyakarta - Tatik (STIE Mandala Jember, 2020)
This study aims to analyze the implementation of transfer pricing policies on CV ABC Yogyakarta. This research uses a qualitative approach with a case study method. The data used are primary data sourced from direct observation, and documentation of financial records. The results showed the transfer price set by the company using the market price method. Market prices are considered an appropriate method of determining transfer prices because products transferred between divisions are in the external market as well. However, in the calculation of the contribution margin of the Division that transfers the product it needs to be re-evaluated. Overheads have not yet been calculated in calculating the contribution margin.